Fuzzy Logic Based Automatic Chili Plant Watering and Pest Monitoring Using the Internet of Things (IoT) - Najib, Nandy Rizaldy; Tahir, Muhammad; Loloallo, Reginald; Syahban, Aditya Rahmat (Indonesian Journal of Advanced Research, 2025)
A challenge many chili farmers currently face is how to streamline watering from manual to automatic for more effective chili plants. This research aims to streamline water use by utilizing fuzzy logic and the Internet of Things (IoT). The method used begins with modeling in fuzzy logic and pest monitoring program code, connecting the system to an Android device. Test results show that the soil moisture sensor is capable of detecting soil moisture in various conditions, both dry and wet. The error tends to be slightly larger due to the increased sensor sensitivity with an average accuracy error below 5%. This sensor is very suitable as an automatic monitoring tool, especially for determining the need for automatic plant watering.